Combination efficiencies of allyl isothiocyanate and triacetyle – β cyclodextrin - Wespetal, Anne (My University, 2015)
University of Wisconsin--Stout. Research Services
Color poster with text, graph, and photographs.
Keywords: bacteria inhibitors; AITC; physical encapsulation; film manufacturing; TAβCD; solvent encapsulation; allyl isothiocyanate; triacetyle – β cyclodextrin; Microencapsulation; Food--Packaging; Posters